Upregulated FoxO1 promotes arrhythmogenesis in mice with heart failure and preserved ejection fraction - Thassio Mesquita; Rodrigo Miguel-dos-Santos; Weixin Liu; Mario Fournier; Russell G. Rogers; Jocelyn Alfaro; Asma Nawaz; Lizbeth Sanchez; Xaviar M. Jones; Liang Li; Eduardo Marbán; Eugenio Cingolani (Nature Communications, 2025)
Abstract Myocardial fibrosis leads to cardiac dysfunction and arrhythmias in heart failure with preserved ejection fraction (HFpEF), but the underlying mechanisms remain poorly understood. Here, RNA sequencing identifies Forkhead Box1 (FoxO1) signaling as abnormal in male HFpEF hearts. Genetic suppression of FoxO1 alters the intercellular communication between cardiomyocytes and fibroblasts, alleviates abnormal diastolic relaxation, and reduces arrhythmias. Targeted downregulation of FoxO1 in activated fibroblasts reduces cardiac fibrosis, blunts arrhythmogenesis and improves diastolic function in HFpEF. These results not only implicate FoxO1 in arrhythmogenesis and lusitropy but also demonstrate that pro-fibrotic remodeling and cardiomyocyte-fibroblast communication can be corrected, constituting an alternative therapeutic strategy for HFpEF.